Initial LOFAR observations of epoch of reionization windows II. Diffuse polarized emission in the ELAIS-N1 field - Jelic, V; de Bruyn, A; Mevius, M; Abdalla, F; Asad, K; Bernardi, G; Brentjens, M; Bus, S; Chapman, E; Ciardi, B; Daiboo, S; Fernandez, E; et al. (EDP Sciences, 2014)
Aims. This study aims to characterise the polarized foreground emission in the ELAIS-N1 field and to address its possible implications for extracting of the cosmological 21 cm signal from the LOw-Frequency ARray-Epoch of Reionization (LOFAR-EoR) data. Methods. We used the high band antennas of LOFAR to image this region and RM-synthesis to unravel structures of polarized emission at high Galactic latitudes. Results. The brightness temperature of the detected Galactic emission is on average ~4 K in polarized intensity and covers the range from-10 to + 13 rad m-2 in Faraday depth. The total polarized intensity and polarization angle show a wide range of morphological features. We have also used the Westerbork Synthesis Radio Telescope (WSRT) at 350 MHz to image the same region. The LOFAR and WSRT images show a similar complex morphology at comparable brightness levels, but their spatial correlation is very low. The fractional polarization at 150 MHz, expressed as a percentage of the total intensity, amounts to 1.5%. There is no indication of diffuse emission in total intensity in the interferometric data, in line with results at higher frequencies Conclusions. The wide frequency range, high angular resolution, and high sensitivity make LOFAR an exquisite instrument for studying Galactic polarized emission at a resolution of ~1-2 rad m-2 in Faraday depth. The different polarized patterns observed at 150 MHz and 350 MHz are consistent with different source distributions along the line of sight wring in a variety of Faraday thin regions of emission. The presence of polarized foregrounds is a serious complication for epoch of reionization experiments. To avoid the leakage of polarized emission into total intensity, which can depend on frequency, we need to calibrate the instrumental polarization across the field of view to a small fraction of 1%. © 2014 ESO.